Oversized RF windows with traveling H-waves in the dielectric area - Shemelin, V.D. (Вопросы атомной науки и техники, 1999)
A method of constructing the adapter from one-mode to oversized waveguide, that creates a prescribed distribution of higher order modes in the output channel, is proposed. Variants of oversized waveguide window with one and three Н-modes in dielectric are discussed, the modes can be shifted by phases.